About Scholarly Works in the Field of Islamic Economic Law: A Visualization of Related Topics - Ahmad Abbas; Manswab Mahsen Abdulrahman (Rumah Jurnal STAIN Majene, 2023)
Understanding issues raised in academic literature is a critical step in developing scholarly works in the field of Islamic economic law. This study aims to explore the topics and trends in the field of Islamic economic law in the last three decades, from 1992–2021. The data used in this study were online published articles from 1992 to 2021. Harzing’s Publish or Perish (PoP), VOSViewer, and Open Knowledge Maps were tools utilized for processing and analyzing the data. 169 articles were retrieved by applying the keyword and title word